2019
DOI: 10.1186/s13018-019-1122-0
|View full text |Cite
|
Sign up to set email alerts
|

High cure rate of periprosthetic hip joint infection with multidisciplinary team approach using standardized two-stage exchange

Abstract: BackgroundTwo-stage exchange arthroplasty is still the preferred treatment choice for chronic PJI. However, the results remain unpredictable. We analyzed the treatment success of patients with an infected hip prosthesis, who were treated according to a standardized algorithm with a multidisciplinary team approach and evaluated with a strict definition of failure.MethodsIn this single-center prospective cohort study, all hip PJI episodes from March 2013 to May 2015 were included. Treatment failure was assessed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 48 publications
4
37
0
8
Order By: Relevance
“…Implant-associated infections represent one dreaded complication in orthopedics. They occur as a result of contamination during or immediately after surgery or at later periods following hematogenic spread [1][2][3]. Numbers of implantations, in general, are growing because of an aging population, increasing obesity, and other predisposing factors [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implant-associated infections represent one dreaded complication in orthopedics. They occur as a result of contamination during or immediately after surgery or at later periods following hematogenic spread [1][2][3]. Numbers of implantations, in general, are growing because of an aging population, increasing obesity, and other predisposing factors [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, worldwide rising bacterial resistance against antibiotics [8][9][10][11] and further, the irreversible adhesion of bacteria and production of extracellular matrix in biofilm formation on the implant surface (infection cause) complicate a successful treatment [12][13][14]. This challenge is still accomplished by using high systemic doses of antibiotics for several months, accepting adverse side effects [1,15,16]. Apart from intensive costs, this leads to high burdens for the patient as well as risks like amputation of the affected limb or even death in case of treatment failure [5,17].…”
Section: Introductionmentioning
confidence: 99%
“…7 Knowing this, it can be deduced that a similar model may prove to be even more effective for the treatment of the most difficult complication of total joint arthroplasty; PJI. There is evidence in the literature to support this claim as well [11,15]. Ntalos et al studied the effect of establishing a weekly multidisciplinary infection conference consisting of orthopedic surgeon, pathologists, microbiologists, and radiologists and found that it led to significant differences in treatment plans.…”
Section: Multidisciplinary Approachmentioning
confidence: 99%
“…До сих пор существуют различные подходы к лечению ППИ и многие моменты его тактики остаются дискуссионными: оптимальный интервал между операциями, критерии купирования воспаления и необходимость пункции перед реимплантацией, значение положительной культуры на втором этапе, длительность антибактери-альной терапии. Для достижения оптимального результата лечения ППИ необходимы эффективные, своевременные и индивидуальные диагностика и лечение в рамках междисциплинарного сотрудничества [5,6,7,8,9].…”
unclassified